The Role and Function of Learning Motivation in Improving Student Academic Achievement - Putra Suharnadi; Neviyarni S; Herman Nirwana (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Motivation is a force that moves a person to achieve a goal and is very important for students because it can increase their enthusiasm for learning. Motivation to learn in all aspects of learning is very important to improve student achievement in certain subjects. The research method used is library research which is online and can be accessed permanently in the library/reading room. The future learning process mainly depends on one factor: motivation, because motivation supports, stimulates and encourages learning. . Research based on direct observation shows that highly motivated students often try harder, appear brave or never give up, actively read and try to improve their academic achievement, and are able to solve problems that arise. The passion that motivates someone to learn is called learning motivation. Motivation can come from within (intrinsic motivation) or from outside (extrinsic motivation). A person's level of motivation influences his behavior in areas of life such as studying and working.